Reframing healthy food choices: a content analysis of Australian healthy eating blogs - Mete, Rebecca (BMC Public Health, 2019)
BACKGROUND: Blogs are widely being used by health professionals and consumers to communicate and access nutrition information. There are numerous benefits for dietitians to establish and contribute to healthy eating blogs. In particular, to disseminate evidence-based nutrition information to promote healthier dietary practices. The aim of this study was to explore characteristics of popular healthy eating blogs and inform the provision of healthy eating information in the Australian context. METHODS: A content analysis approach was used to identify characteristics of popular Australian healthy eating blogs. A purposive and snowball sampling approach was used to identify healthy eating blogs from search engines including Google, Bing and Yahoo. Blogs were deemed eligible if: (1) the author self-identified as a health professional; (2) the blog was written by a single author; (3) the blog was written by an Australian author; (4) the blog had a minimum of one post per month, and (5) the blog focused on communicating healthy eating information to the general adult population. RESULTS: Five popular blogs were followed over a three-month period (December 2017–March 2018), with 76 blog posts included for analysis. Characteristics of these popular blogs were examined and four main features were identified: (i) clearly conveying the purpose of each post; (ii) developing a strong understanding of the reader base and their preferences; (iii) employing a consistent writing style; use of vocabulary and layout; and (iv) communicating healthy eating information in a practical manner. These findings reveal important insight into the features that promote effective nutrition communication within this context. CONCLUSION: Findings from this study highlight common characteristics of popular healthy eating blogs. Future research into the development of blog guidelines which incorporate the characteristics identified in this study can support dietitians in establishing or contributing to the successful provision of evidence-based nutritional information through blogs.